A low pre-existing anti-NS1 humoral immunity to DENV is associated with microcephaly development after gestational ZIKV exposure. - Sebastián Castro-Trujillo; William R Mejía; Katherine Segura; Juanita Castro-Meneses; Rocío Vega; Doris Salgado; Carlos E Fonseca; Ángela M Ortiz; Federico Perdomo-Celis; Irene Bosch; Carlos F Narváez (PLoS Neglected Tropical Diseases)
Background Gestational Zika virus (ZIKV) infection is associated with the development of congenital Zika syndrome (CZS), which includes microcephaly and fetal demise. The magnitude and quality of orthoflavivirus-specific humoral immunity have been previously linked to the development of CZS. However, the role of ZIKV NS1-specific humoral immunity in mothers and children with prenatal ZIKV exposure and CZS remains undefined. In addition, considering that most of the at-risk population lives in dengue virus (DENV)-endemic areas, it is not clear what is the association between pre-existing DENV NS1-specific humoral immunity and CZS. Methods Here, we studied 328 mothers and children with a clinical diagnosis and seropositivity for ZIKV infection during pregnancy, included during the 2015-2016 ZIKV epidemic in Colombia. We also performed clinical evaluation and pediatric neurological follow-up. The relative levels of circulating NS1-specific IgM and IgG against ZIKV and DENV were evaluated in mothers and children, and the association with the development of microcephaly was analyzed. Results DENV and ZIKV IgG-NS1 antibodies in pregnant women were placentally transferred, and this passage and its duration in children depended on the maternal levels of the antibodies. We reported that higher concentrations of pre-existing DENV, but not ZIKV IgG-NS1 antibodies, were associated with a reduced risk of CZS-related microcephaly. Also, we observed that the IgM-NS1 response in infants is long-term and has a minor association with poor outcomes. Conclusions The development of microcephaly in children prenatally exposed to ZIKV is associated with low plasma levels of placentally transferred, pre-existing DENV IgG-NS1 antibodies. These data are compatible with a protective role of anti-NS1 IgG antibodies against ZIKV infection during pregnancy and highlight the promising role of NS1 as an orthoflavivirus vaccine target in high-risk populations.